Processing of high-resolution temporal climate data for daily simulations of a complex agro-ecosystem - Paz, Maria Catarina (2021)
Ecosystem services, such as natural pest control, are essential tools to be incorpora ted in future agricultural methodologies. In this paper we focus on the processing of climate data series that feed to a system of computer models simulating daily inte ractions of a pest and its predator, in a dynamic landscape, the olive grove. We filled hourly climate data series and converted them to daily climate series using R langua ge. The methodology used produces acceptable climate data series for the system to run and allows to segregate specific periods of the day while maintaining daily tem poral resolution. We expect this paper can be helpful when dealing with similar data and purpose.